Growth and renal function dynamics of renal oncocytomas in patients on active surveillance. (9th August 2021) - Neves, Joana B.; Varley, Rebecca; Agnesi, Stefano; Withington, John; Rodrigues, Filipe B.; Warren, Hannah; Yuminaga, Yuigi; Capitanio, Umberto; Rode, Nicola; Grant, Lee; Tran‐Dang, My‐Anh; El‐Sheikh, Soha; et al.
Abstract : Objectives: To study the natural history of renal oncocytomas and address indications for intervention by determining how growth is associated with renal function over time, the reasons for surgery and ablation, and disease‐specific survival. Patients and Methods: The study was conducted in a retrospective cohort of consecutive patients with renal oncocytoma on active surveillance reviewed at the Specialist Centre for Kidney Cancer at the Royal Free London NHS Foundation Trust (2012 to 2019). Comparison between groups was performed using Mann–Whitney U ‐tests and chi‐squared tests. A mixed‐effects model with a random intercept for patient was used to study the longitudinal association between tumour size and estimated glomerular filtration rate (eGFR). Results: Longitudinal data from 98 patients with 101 lesions were analysed. Most patients were men (68.3%) and the median (interquartile range [IQR]) age was 69 (13) years. The median (IQR) follow‐up was 29 (26) months. Most lesions were small renal masses, and 24% measured over 4 cm. Over half (64.4%) grew at a median (IQR) rate of 2 (4) mm per year. No association was observed between tumour size and eGFR over time ( P = 0.871). Nine lesions (8.9%) were subsequently treated. Two deaths were reported, neither were related to the diagnosis of renal oncocytoma. Conclusion: Natural history data from the largest active surveillance cohort of renal oncocytomas to date show that renal function does not seem to be negatively impacted by growing oncocytomas, and confirms clinical outcomes are excellent after a median follow‐up of over 2 years. Active surveillance should be considered the 'gold standard' management of renal oncocytomas up to 7cm.